Discharge transition experienced by older Korean women after hip fracture surgery: a qualitative study - Young Ji Ko; Ju Hee Lee; Seung-Hoon Baek (BMC, 2021)
Abstract Background This study aimed to explore older Korean women's discharge transition experiences after hip fracture surgery. Methods This was a descriptive qualitative study. Face-to-face interviews following hip fracture surgery were conducted on 12 women aged 65-87 years. Data were collected 1 to 2 days before discharge and again 4 weeks after discharge following hip fracture surgery, and were analyzed using qualitative content analysis. Results Four main themes were identified: (1) challenge of discharge transition: unprepared discharge, transfer into other care settings, and eagerness for recovery; (2) physical and psychological distress against recovery: frail physical state and psychological difficulties; (3) dependent compliance: absolute trust in healthcare providers, indispensable support from the family, and passive participation in care; and (4) walking for things they took for granted: hope of walking and poor walking ability. Conclusions After their hip fracture surgeries, older women hoped to be able to walk and perform simple daily chores they previously took for granted. Considering the physical and psychological frailty of older women undergoing hip surgery, systematic nursing interventions including collaboration and coordination with other healthcare professionals and settings are necessary to ensure the quality of continuous care during their post-surgery discharge transition. Encouraging partial weight bearing and initiating intervention to reduce fear of falling at the earliest possible time are essential to attain a stable discharge transition. Additionally, older women should be invited to participate in their care, and family involvement should be encouraged during the discharge transition period in South Korea.